R Rancang Bangun Aplikasi Evaluasi Pengangkatan Kepala Desa Pada Badan Pemberdayaan Masyarakat Dan Pemerintah Desa Kabupaten Garut - Usep Abdul Rosid; Maulana, Haisyam (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Information technology has now experienced quite rapid development compared to before. Technological developments occur continuously as humans develop the technology to be more sophisticated and easy to use by humans. In all aspects of life, it is very necessary to have a computerized system in the form of a good application program and easy to operate. Because with the application program, it will provide the accuracy of the information needed and reduce the level of information errors. Seeing these reasons, the Design and Development of the Evaluation Application for the Appointment of Village Heads at the Garut Regency Community and Village Government Empowerment Agency (BPMD) needs to be made to get appropriate and appropriate results in obtaining information. This Application Design and Development can assist the Implementation Staff in the Village and Village Government Sub-Sector in evaluating the elected village head until the Regent's Decree on the appointment of the village head, and providing appropriate and appropriate reports For the stages in making this application design, interviews were conducted with the executive staff of the Village and Village Government sub-division and direct observation of the ongoing village head appointment system. The application program is made using visual basic 6.0 with a Data Flow Diagram design as an overview of the system flow.